Techno-economics of desalination cogeneration with SMR: Case study for prospective NPP in West Kalimantan - Siti Alimah; Sudi Ariyanto; Erlan Dewita; Sriyono; Djati Hoesen Salimy; Akhmad Muktaf Haifani; Donny Nurmayady; Farisy Yogatama Sulistyo; Euis Etty Al-Hakim (Case Studies in Chemical and Environmental Engineering, 2024)
The Small Modular Reactor emerges as a recommended technology for nuclear power plant (NPP) development in West Kalimantan, particularly at the Pantai Gosong site. NPP demand highly purified water for cooling system, while seawater contains high TDS, so desalination by utilizing heat and power from NPP, offers a viable solution. Additionally, desalination products can supply freshwater to communities within a 10 km radius, including Sungai Raya and Sungai Raya Island Districts. This study aims to determine the techno-economic aspect of desalination cogeneration with SMR-type NPP for West Kalimantan. The methodologies in this research encompass a comprehensive literature review, a qualitative assessment of desalination technology, and a quantitative economic analysis utilizing the DEEP version 5.1. Techno-economic analysis shows that the simple payback period for MED is 12.3 years, while MSF is 13.9 years. Power lost at MED is 5.3 MWe, while MSF is 9.1 MWe. At a temperature of 30.7 °C, the total water cost of the MED is $1.277 $/m3, while MSF is $1.595 $/m3. MED desalination with temperature 70 °C can be effective using residual heat as an energy source. Cogeneration of MED technology can be option for utilization of heat and power in the context of NPP development in West Kalimantan.